Formation, mechanism and significance of alluvial‐dammed lakes in Golmud River catchment, north‐eastern Qinghai‐Tibetan Plateau. Issue 12 (21st July 2021) - An, Fuyuan; Chen, Tianyuan; Li, Xiangzhong; Liu, Xiangjun; Wang, Yixuan; Chen, Zongyan; Chongyi, E
Abstract: This study investigated a series of dammed lakes and downstream‐adjacent alluvial fans in the upstream to middle reaches of the Golmud River in the eastern Kunlun Mountain, on the north‐eastern Qinghai‐Tibetan Plateau (QTP). An optically stimulated luminescence (OSL) chronology shows the sediments of five dammed lakes developed from c . 45–40, 30–25, 18–14, and 12–8 ka, corresponding to MIS 3b, late MIS 3a, Last Deglaciation, and early Holocene, respectively. The remote sensing data show these dammed lakes have a total area of 109.4 km 2, with the lake volume of more than 4.0 km 3 . Symmetric alluvial fans from north–south tributary valleys produced OSL ages of c . 61–52, 42–31, 26–20, and 16–10 ka, corresponding to glaciation periods: the MIS 3c and MIS 3a, MIS 2, and the Last Deglaciation. This suggests that glacial activity is responsible for the alluvial fan development, where dammed rivers occurred first, but lake formation did not take place synchronously until later periods of strong hydrologic activity, resulting from northward intrusions of the Indian summer monsoon (ISM) or glacier melt. Thus, the blocking pattern is that river valleys were dammed during periods of glacial activity and lakes formed during wet periods. The lake formation and subsequent drainage may have resulted in: (i) impeded headwater incision and strengthening of downstream dissection; (ii) enriched the halite and potash in the distal Qarhan Salt Lake through hydrologic and hydrochemical processes of abundant water input, the salt lake expansion, salt redissolution from playa and final resedimentation during later dry periods. The alluvial‐dammed lake pattern in the mountain‐basin systems of eastern Kunlun Mountain offers a model for assessing the linkages between monsoon dynamics, geomorphic processes and distal salt lake evolutions in other arid regions. Abstract : Landscape evolution processes in the mountain‐basin system of the Golmud River catchment: (a) During glacial advance stages, massive outwash‐origin detritus is produced by glacier cascades to lateral alluvial fans in tributary valleys. Coalescence of north‐south symmetric alluvial fans forms dams in the main river valley, and the distal salt lake shrinks; (b) During wet stages, the Indian summer monsoon intrudes northward and abundant precipitation forms surface runoff. Dammed lakes develop behind the preexisting alluvial dams; (c) After subsequent dam failure, high runoff input causes salt lake expansion, clast input and salt minerals redissolution from playa; (d) During later dry climatic stages, salt minerals accumulate from the playa owing to shrinkage of the salt lake.